Impact of Innovative Leadership on Employees Performance - Iskander A. Sattar; Rokia Abdullah Mohammed Alsomaid; Hend Ahmed Ali Musallam Bagnaf; Rana Muneer Noman Ghalib (مجلة الدراسات الاجتماعية)
The main objective of this study is to identify the relationship between innovative leadership and employee performance within a banking institution in Aden- Yemen which is ( Al-Qutaibi Islamic Bank )Where the problem statement was represented to answer the following question : What is the impact of innovative leadership with it’s dimensions on employees performance with it’s dimensions in the banking sector targeting (Al-Qutaibi Islamic Bank -Aden)?  The researchers used the descriptive analytical method and statistical program (SPSS) to determine the sample items, there were 60 questionnaires that was used for the analysis. The sample appropriate for study was 51 questionnaires after excluding the 9 invalid ones. Results showed that Employees reported positive perceptions of innovative leadership practices, with high average scores in empowerment, communication, creativity, and collaboration.  This study concluded that Innovative leadership styles emphasises on empowerment, communication, creativity, and collaboration to have a significant positive impact on employee perception and performance in a banking environment. The study recommends developing methods that can be used to measure innovation performance. The study relies on self-reported data and focuses on a single organization. Future studies could explore objective measures of innovation and expand research to other industries.